Discovery of a macromolecular complex mediating the hunger suppressive actions of cocaine: Structural and functional properties. (8th February 2021) - Casanovas, Mireia; Jiménez‐Rosés, Mireia; Cordomí, Arnau; Lillo, Alejandro; Vega‐Quiroga, Ignacio; Izquierdo, Joan; Medrano, Mireia; Gysling, Katia; Pardo, Leonardo; Navarro, Gemma; Franco, Rafael
Abstract: Cocaine not only increases brain dopamine levels but also activates the sigma1 receptor (σ1 R) that in turn regulates orexigenic receptor function. Identification of interactions involving dopamine D1 (D1 R), ghrelin (GHS‐R1a ), and σ1 receptors have been addressed by biophysical techniques and a complementation approach using interfering peptides. The effect of cocaine on receptor functionality was assayed by measuring second messenger, cAMP and Ca 2+, levels. The effect of acute or chronic cocaine administration on receptor complex expression was assayed by in situ proximity ligation assay. In silico procedures were used for molecular model building. σ1 R KO mice were used for confirming involvement of this receptor. Upon identification of protomer interaction and receptor functionality, a unique structural model for the macromolecular complex formed by σ1 R, D1 R, and GHS‐R1a is proposed. The functionality of the complex, able to couple to both Gs and Gq proteins, is affected by cocaine binding to the σ1 R, as confirmed using samples from σ1 R −/− mice. The expression of the macromolecular complex was differentially affected upon acute and chronic cocaine administration to rats. The constructed 3D model is consistent with biochemical, biophysical, and available structural data. The σ1 R, D1 R, and GHS‐R1a complex constitutes a functional unit that is altered upon cocaine binding to the σ1 R. Remarkably, the heteromer can simultaneously couple to two G proteins, thus allowing dopamine to signal via Ca 2+ and ghrelin via cAMP. The anorexic action of cocaine is mediated by such complex whose expression is higher after acute than after chronic administration regimens. Abstract : Cocaine binds to sigma1 receptors, which form a functional complex together with dopamine D1 and ghrelin GHS‐R1a receptors. The proposed structure of the molecular complex contains two G proteins and allows cocaine to affect the actions of dopamine and ghrelin. The anorexic action of cocaine is mediated by the complex, whose expression is greater after acute than after chronic administration regimens.